Peran Guru dalam Mengajarkan Menjahit pada Anak Gangguan Spektrum Autisme di YPPA Padang - Devindra, Yufilda; Rahmahtrisilvia, Rahmahtrisilvia (Universitas Negeri Padang, 2023)
The research objective is to describe the teacher's role in prohibiting sewing on ASD children. This research is descriptive research with a qualitative approach. The subjects were Mrs EY and Mrs RY. The research was conducted during sewing skills learning in the even semester of the 2022-2023 academic year. The teacher`s role as an informant is to inform skills that will be learned. The teacher`s roles as an organizer is to provide learning tools. The teacher's roles as a motivator is open slavery to encourage students for practicing sewing. The teacher's roles as a director is to provide direction for sewing. The teacher's roles as a transmitter is to set the student's sewing position. The teacher as an initiator is to provide ideas for sewing. The teacher roles as a mediator is to provide learning media for sewing. The teacher`s roles as an evaluator is to evaluate learning to sew.